Impact of mobile health-based nutritional education on hemoglobin levels in anemic adolescent girls in rural Bangladesh: a randomized controlled trial - Md Jiaur Rahman; Md Moshiur Rahman; Mohammad Habibur Rahman Sarker; Ryota Matsuyama; Masayuki Kakehashi; Miwako Tsunematsu; Mohammad Ali; Ashir Ahmed; Mohammad Delwer Hossain Hawlader; Hiromi Kawasaki; Yoko Shimpuku (BMC Public Health)
Abstract Background Anemia is a global public health concern, particularly among adolescent girls in rural Bangladesh, owing to inadequate knowledge and insufficient nutritional intake. Mobile health (mHealth) education has the potential to solve these limitations. This study aimed to evaluate the impact of mHealth education on raising hemoglobin levels and reducing anemia among adolescent girls in rural Bangladesh. Methods This open-label, parallel-group, randomized controlled trial was conducted at two schools in Chandpur district, Bangladesh from late May 2022 to January 2023. We randomly assigned one school to the intervention group and another to the control group and then performed simple random sampling to recruit 138 adolescent girls with anemia from the intervention (n = 69) and control (n = 69) groups. The intervention group received online counseling sessions and health education via mHealth technology, whereas the control group received usual care, and both groups were observed for 8 months. We performed mixed-effects model and generalized estimating equations (GEE) to evaluate the outcomes. Results The study analyzed 121 participants (intervention group, 62; control group, 59). After adjusting for covariates, mixed-effects model observed that body mass index (BMI) [coefficient: 1.10, 95% confidence interval (CI): 0.44–1.76, P = 0.001], mid-upper arm circumference (MUAC) (coefficient: 0.77, 95% CI: 0.27–1.26, P = 0.002), hip circumference (coefficient: 2.24, 95% CI: 0.62–3.87, P = 0.007), and waist circumference (coefficient: 2.20, 95% CI: 0.74–3.66, P = 0.003) were significantly improved in intervention group. Although hemoglobin levels improved in the intervention group, the change was not statistically significant. However, the intervention group experienced a higher anemia recovery than the control group (25.8% vs. 13.6%). The GEE showed improvement in knowledge (coefficient: 4.11, 95% CI: 3.63–4.58, p = < 0.001), attitude (coefficient: 1.59, 95% CI: 1.24–1.96, p = < 0.001), and practice (coefficient: 0.39, 95% CI: 0.13–0.66, p = 0.004) in the intervention group compared to the control group after adjusting for relevant covariates. Conclusions The mHealth education led to improvements in knowledge, attitude, and practice (KAP) scores related to anemia among adolescent girls. Furthermore, the intervention resulted in improvements in BMI, MUAC, and hip and waist circumference measurements. Additionally, there were positive trends indicating a reduction in anemia prevalence, accompanied by an upward trend in hemoglobin levels. Therefore, implementing this strategy could enhance KAP and contribute to reducing adolescent girls’ anemia in low-resource settings. Trial registration NCT05185661 ( https://www.clinicaltrials.gov/ ), registered [January 11, 2022] with ClinicalTrials.gov.